Web-based counselling system / Suvarna Supramaniam - Suvarna , Supramaniam (2002)
Web counselling has brought us in a new virtual world of communication and solving problems together. Computer counseling has already evolved before the web has taken its roots. Initially it was more on programs which counsels and acts like educators. When the web evolved, online counselling was introduced where there were many mediums fro communication and counselling available. More people, who know the web, started experimenting on this medium for communication and counselling. Now, since most people who log on the web were there for communication like e-mail, chat and forum rather than finding information, e-mail servers like hotmail and yahoo has been clogged up with millions of people, who chat and e-mail among themselves everyday. Counselling ts important for all people, as it is healthy to solve personal problems with a person who we are comfortable with. Information about relationship and other aspects of life on web can help overcome problems without a counsellor being available. A search engine for finding this huge resource will be one suitable solution. Counselling can also be the solution for a certain business, which can help many people to choose the right solution, for example: buying property, financial and choosing the right computer package. This web counselling system helps to provide the right solution for each individual through the search capability. It also has chat, making appointments before meeting and forum facility, which alternates the communication medium. One of the most interesting features on this system is the implementation of the web robot, which acts as counsellor during your visiting sessions. Another feature is the system has the capability to run even if the counsellors are not around through search engine. Research can generate graphs by collecting data, is another important feature of this system. This web counselling system hopes to overcome current problems when compared to the current system such as the availability of information. It also explores on the search methodology and algorithm.